Blogging: Innovation in an EFL reading and writing class - Fatemeh Nikui Nezhad (Teaching English Language, 2007)
Computer-mediated learning tools have promised to be effective educational tools in language classes. This research focused on integrating tutor weblog and learner blogs into reading and writing English classes. This quasi-experimental study was conducted on 57 Iranian freshman high school students at Farzanegan Highschool. Data was obtained through a Likert scale attitude questionnaire and ten open-ended or yes-no questions regarding the effectiveness of Blog Assisted Language Learning (BALL). Data were analyzed using Chi-square test with SPSS. The results of data analysisindicated that the vast majority of students found the task of using and creating blogs appealing. They preferred weblog writing to the more traditional ways. Most of them believed that weblogs can improve their reading and writing skills. The students perceived that the interaction and cooperative learning among peers increased due to the blog assignments. This study yielded some practical insights and implications which are presented in this article.